2012
DOI: 10.1007/s10404-012-0946-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic energy harvesting by droplet-based multi-phase microfluidics

Abstract: This paper presents an energy scavenging technique, merging microfluidics with electrostatic energy harvesting. The method employs droplet-based microflow of two phases with different electrical permittivities, resulting in a capacitance change across the microchannel, to harvest electrical energy. The technique is implemented on 3 mm wide, 1 mm deep minichannels. It is shown that 0.4 nW can be harvested using a single electrode pair, with air and water as the two phases flowing at 1 ml/min. The generated powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This novel fluidic active transducer has several strength points. First, it has very simple structure and fabrication method compared with previous works 6 7 8 9 10 . Second, until now, most of the electricity generators have been water vibrational generators 22 23 24 but FEG can be operated under various channel flow conditions conforming to flows found in daily life and in nature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This novel fluidic active transducer has several strength points. First, it has very simple structure and fabrication method compared with previous works 6 7 8 9 10 . Second, until now, most of the electricity generators have been water vibrational generators 22 23 24 but FEG can be operated under various channel flow conditions conforming to flows found in daily life and in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Specially, interest in electricity generation with flows in a channel has been recently increased in the fields of micro energy harvesting and sensing 6 7 8 9 10 . Several techniques such as variation of capacitance 6 7 , reverse electro-wetting 8 and electro kinetic flow 9 10 have been studied.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bu et al [6] and Choi et al [7] reported on a liquidbased energy harvester, suitable for low vibration frequencies of less than 10 Hz. Others have demonstrated electrostatic energy harvesting that uses the change in capacitance across a microchannel due to the flow of liquids [8], [9]. However, there were limitations in obtaining high output power with those harvesters because of the small and slow change in capacitance.…”
Section: Introductionmentioning
confidence: 99%